Pustakawan Dalam Perspektif Manajer Informasi: Studi Kasus Pada Mahasiswa Jurusan S1 Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Ar-Raniry - Saifuddin Rasyid (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
This study aims to find out Librarian in Perspective of Information Manager (Case Study on Library Science Undergraduate Student of Adab and Humanities Faculty of UIN Ar-Raniry, Banda Aceh). This research uses quality descriptive approach, an approach that emphasizes more on the deductive and inductive deduc- tion process and on the analysis of the dynamics of relationship between observed phenomena, using scientific logic. The students of Library Science were observed to be 54 people for three months. For this research the author will explain in detail about UIN Ar-Raniry Banda Aceh Main Library in the perspective of information managers for llibrary users especially Library Science students class of 2016 intake. The research results are; Librarians are not yet fully able to become information managers at UIN Ar-Raniry Main Library of Banda Aceh, due the small number of librarians for this size of a college library. Lack of librarian contribution to be- come information manager, in order to be able to fulfill requirement of information for their users, in this case undergraduate student of Library Science. Regarding the perspective that a library must be able to provide all forms of information required has not been done well, especially the information needs fot this such of users in this case Library Science students.